Bimbingan Intensif Dasar Keislaman Santri Baru DPUQ Mambaul Ulum Bata-Bata - Latifatul Mahbubah; Ach. Mahfudz Abd. Qadir; Didin Burhanuddin Rabbani (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2025)
Intensive basic Islamic guidance is an activity aimed at new students in the Ulumul Qur'an Development Division (DPUQ) of the Mambaul Ulum Bata-Bata Pamekasan Islamic Boarding School. This activity aims to help new students understand and master basic Islamic knowledge in the form of Tauhid, Fiqh and Imla'. This activity uses the Participatory Action Research (PAR) method which focuses on participation and collaboration with senior students at the Islamic boarding school. The results of this activity show that the new students have understood and mastered the material well, accompanied by their ability to demonstrate arguments relevant to the material. The results of the activity also showed that the new students were able to write Arabic script well, both letter by letter and in the form of simple sentences